Indústria cultural e educação: a análise das personagens femininas em filmes dos estúdios Disney - Vieira, Bárbara Luisa de Souza (2022)
School and families formally have a well-defined educational role in the lives of students, however, a wide-ranging element of non-formal education is cinema, since it is present in almost all homes and educational establishments. Therefore, it can be seen both as a pedagogical and leisure resource. Films can be understood as products of the cultural industry and, therefore, their producers have interests linked to capital and use ideologies and values as a backdrop for the maintenance of social order, however, the screens need to present an enchantment and transmit values in order to please all audiences and offer what they want to see, as well as taking care not to absorb too much value so that it can hurt others, thus impacting the business. This work is interested in analyzing and comparing the productions for children at Disney Studios aimed at the female audience, focusing on the way in which these productions portray women, which stereotypes are most used, considering the possible impacts that this may have on the way how the female figure changes over time. The classic film Alice in Wonderland (1951) was selected, comparing it with the “Live action”, Alice in Wonderland (2010) and Alice Through the Looking Glass (2016). The collection of information was carried out using the following procedures: elaboration of a research instrument (Analysis Sheet), testing the Analysis Sheet with two other films, Cinderella (1950) and Cinderella (2015), and, after verifying the functionality satisfactory for the analysis of the female characters, a file was made and, later, a second research instrument was used to record the detailed descriptions of the most relevant scenes and passages for the study. The analysis framework was composed by formulations of the authors of the critical theory of society and the main aspect to be highlighted refers to the need for more critical studies and detailed analyzes directed to cinematographic productions with a focus on female characters until finally characteristics of different ways are perceptible of being a woman that are guided by ideals of equality and freedom, as there are different ways of being a woman that are not addressed in the films. The analysis framework was composed of formulations by the authors of the critical theory of society and the main aspect to be highlighted refers to the need for more critical studies and detailed analyzes directed to cinematographic productions with a focus on female characters until the various ways of being a woman that are based on ideals of equality and freedom become perceptible, as there are different ways of being a woman that are not addressed in the films